THE INFLUENCE OF THE CRAFT PRODUCT BRAND ON THE EFFICIENCY OF THE AGRICULTURAL ENTERPRISE IN THE CONDITIONS OF DIGITALIZATION - KRASNORUTSKYY, Oleksiy; YAZLYUK, Borys; STETSENKO, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Craft production is a special sector of entrepreneurship based on creative approaches and close interaction with the consumer. The trend of the development of handicrafts in the agricultural sphere has long been characteristic of Europe and of Ukraine. The use of information technologies allows to expand communications, changes the status of their participants, facilitates spatial interaction in the network. The purpose of the study is to determine the nature of the influence of the craft product brand on the efficiency of the agricultural enterprise in modern conditions of digitalization. It was determined that the business related to the craft product is not relevant for agricultural producers of Ukraine. It has certain development triggers and needs formed in the market. In the conditions of digitalization, the priorities and forms of organization of work with clients are changing significantly, which should be taken into account when building a branding strategy of a craft manufacturer. Attention is paid to issues related to the formation of brand attributes. In the conditions of digitalization, they include those objects that are included in the information field of the brand, and thanks to which the consumer pays attention, perceives the craft product and the space associated with it. The problem points of choosing the name of the company and the product as a component of the brand have been identified. The practice of naming craft agricultural producers of Ukraine was analyzed. Reasoned opportunities and conditions for the use of digital tools in the branding of craft products of an agricultural enterprise, which depend on the purpose of communication and the digital skills of the producer. In modern conditions, a strong brand can perform the function of an airbag, although in crisis situations it will lose part of its value. It is extremely important to invest material and intellectual resources in the formation, development, and promotion of the brand at the very beginning of the craft business. Therefore, the influence of the craft product brand on the efficiency of the agricultural enterprise in the conditions of digitalization is increasing and becoming a prerequisite for success in the future.